Sensitivity of seismically isolated structures. - Politopoulos, Ioannis (Earthquake engineering & structural dynamics.)
In this paper we study the sensitivity of seismically isolated structures to a small variability of the earthquake excitation and of some structural properties with respect to the probability of failure and floor spectra. In particular, the influence of the nonlinear behaviour of the isolated superstructure on the vulnerability and on the floor spectra is investigated by means of a series of Monte Carlo simulations of simple two degrees-of-freedom systems. Several types of passive and active isolation systems are examined and three different idealized nonlinear constitutive laws are considered for the superstructure. It is found that, in general, the probability of failure does not depend on the specific cyclic behaviour of the assumed constitutive law and general trends regarding the impact of different isolation devices on vulnerability are established. As for the floor spectra, the influence of moderate nonlinear behaviour of isolated superstructures, with the exception of the case of a non-dissipative elastic nonlinear law, is negligible, contrary to the case of conventional structures.